2012
DOI: 10.3109/17435390.2012.668569
|View full text |Cite
|
Sign up to set email alerts
|

C60exposure induced tissue damage and gene expression alterations in the earthwormLumbricus rubellus

Abstract: Effects of C₆₀ exposure (0, 15 or 154 mg/kg soil) on the earthworm Lumbricus rubellus were assessed at the tissue and molecular level, in two experiments. In the first experiment, earthworms were exposed for four weeks, and in the second lifelong. In both experiments, gene expression of heat shock protein 70 (HSP70) decreased. For catalase and glutathione-S-transferase (GST), no significant trends in gene expression or enzyme activity were observed. Gene expression of coelomic cytolytic factor-1 (CCF-1) did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…van der Ploeg et al (2013) also observed adaptive responses in L. rubellus after C 60 nanoparticle exposure. After 4 weeks, the gut epithelial tissue was damaged, however after lifelong exposure the damage to the gut epithelial tissue was less severe, suggesting activation of tissue repair mechanisms (van der Ploeg et al, 2013). Similar adaptive responses of earthworms to xenobiotics have been observed in other studies as well (Corp and Morgan, 1991;Maity et al, 2008;Spurgeon and Hopkin, 1999).…”
Section: Multivariate Statistical Analysismentioning
confidence: 78%
See 4 more Smart Citations
“…van der Ploeg et al (2013) also observed adaptive responses in L. rubellus after C 60 nanoparticle exposure. After 4 weeks, the gut epithelial tissue was damaged, however after lifelong exposure the damage to the gut epithelial tissue was less severe, suggesting activation of tissue repair mechanisms (van der Ploeg et al, 2013). Similar adaptive responses of earthworms to xenobiotics have been observed in other studies as well (Corp and Morgan, 1991;Maity et al, 2008;Spurgeon and Hopkin, 1999).…”
Section: Multivariate Statistical Analysismentioning
confidence: 78%
“…Toxic responses were observed faster in soil tests as compared to contact tests suggesting that the method of exposure is important in dictating the metabolic response. Soil studies also revealed that after 14 days of exposure, the earthworms potentially exhibited tolerance to C 60 nanoparticles, which revealed adaptive response at the molecular-level complementing the histological adaptive response reported by van der Ploeg et al (2013) in L. rubellus earthworms. The amino acids leucine, valine, isoleucine and phenylalanine, the nucleoside inosine and the sugars glucose and maltose emerged as potential bioindicators of exposure to C 60 nanoparticles and should be analyzed in a targeted manner in future studies to determine their concentration-dependent fluctuations over a wide range of sub-lethal C 60 nanoparticle exposure concentrations.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations